Saúde cardiovascular como tema gerador no curso normal - Lara, Simone (2013)
Cardiovascular diseases represent the first cause of death in Brazil, resulting in high costs to the public health system in the country. It´s known that the most risk factors that take to the development of these diseases occurs due to modifiable lifestyle, such as inadequate nutrition and physical inactivity, and they´re present from childhood. Therefore, it´s important that the issues involving the practice of healthy lifestyle are addressed at school so early, in order to prevent these diseases at older ages. However, for that these health education processes are effective at school in these early stages of learning, their teachers must be properly prepared for this task. Thus, the aim of this study was to discuss the health transversal theme, using the cardiovascular health generator theme with students in the normal course, future children´s educators and of the early years. To achieve this goal, some methodological tools were used, such as the physical profile evaluation of the student and the use of images on the theme. Thus, we start from own body measurements of student to be closer to the cardiovascular health generator theme, and we use the images because it´s a fun methodology and widely used by students in the normal course. We observed, according to the criteria examined, that these students didn´t constitute as a risk profile for developing cardiovascular diseases (anthropometrics appropriate), despite the physical activity being below the levels suggested for healthy individuals. Furthermore, we met a low understanding of young people about the cardiovascular health perceptions through the images used, this fact may be associated with a important deficit in addressing these issues in the current training of these students. Thus, after the discussions in large group about the proper meaning of the cardiovascular health images, as well as the explanation of the relation between physical measurements with health profile, it was found that learning was more meaningful. Thus, at a later time, the students built a didactic material, consisting of recreational activities about the studied themes for later application to early years. As a result, we realized the wealth of didactic material created by students, it was verified by creative and playful nature found in activities. Through the application of recreational activities built by students in the normal course to the early years, it was observed the effective participation of children through questions and curiosities, engaging in recreational and practices activities, and a important learning about the issues verified through their reports. Finally, the most appropriated knowledge about the cardiovascular health generator theme, and issues related to health promotion and cardiovascular disease prevention by students in the normal course and the early years were some contributions of this study to improve the teaching and learning process in science and health education.